A genetic based algorithm for the quadratic 0-1 problem - Schütz,G. (2003)
In this work we present an algorithm to the unrestricted binary quadratic program. This approach combines genetic operators with greedy and heuristic procedures. We started from a genetic based algorithm and replaced the random mutation by a greedy procedure based on each variable contribution to the objective function. We also introduced in the genetic population an individual obtained by a heuristic that finds a local star minimum point. Computational experience with a set of test-problems, known from literature, is reported and analysed. Our results are quite promising.